EFFECT OF GRAZING BY THE RABBITFISH, SYGANUS SP., ON THE YIELD OF THE CARAGEENIN PRODUCING ALGA, EUCHEUMA SPINOSUM, AND REDUCTION OF HERBIVORY BY THE PRESENCE OF HALIMEDA SPP. - Izzati, Munifatul (My University, 1993)
Eucheuma spinosum is an agar (carrageenin) producing marine alga of commercial value in several countries, including Indonesia. However, its crop yield is often reduced by herbivores. In many areas, herbivores consume almost 100 percent of Eucheuma production. I investigated one way of protecting Eucheuma by application of intercropping of Eucheuma spinosum and Halimeda sp., an unpalatable alga. Laboratory and field experiments were conducted in Indonesian coastal waters. The field experiments were conducted in two areas differing in densities of the main grazer, Syganus, the rabbitfish. In the laboratory Eucheuma was significantly less consumed by Syganus sp. when associated with Halimeda. In the field, I tested two intercropping arrangements: In one, plants of Halimeda and Eucheuma were arranged at 10 cm from each other and in the other they were in direct contact. Results indicate that intercropping with Halimeda reduced density of Syganus and significantly enhanced the production of Eucheuma. At a site where Syganus density was very low, the difference between control and intercropping treatment was not significant. At sites with high Syganus density, the fish consumed all of Eucheuma in controls, while the intercropped plants survived. It is suggested that in habitats where grazing by herbivores causes local extinction, association with Halimeda can present a significant survival strategy for Eucheuma.
Keywords: Sygamus sp.; Algae; Halimeda sp.; Herbivores; Grazing